Dermoscopy, a useful tool for general practitioners in melanoma screening: a nationwide survey3. (30th June 2016) - Chappuis, P.; Duru, G.; Marchal, O.; Girier, P.; Dalle, S.; Thomas, L.
Summary: Background: Dermoscopy improves diagnostic accuracy in melanoma, as shown by several meta‐analyses. Although it is used by general practitioners (GPs) in Australia, Canada and Italy, no published data on this topic are available in France. Objectives: To review the opinions and use of dermoscopy by GPs in France and to understand their practice of skin examination. Methods: We designed a descriptive and cross‐sectional survey and conducted it between 26 November and 26 December 2014. An anonymous, multiple‐choice questionnaire about the demographic characteristics, skin examination modalities and use and training in dermoscopy was sent to 4057 GPs in four large regions of France. Pearson, χ 2, Student, Welch and Fisher tests were used for cross‐tabulation statistical analysis. Results: Only 8% of respondents had access to a dermoscope; most were male practitioners and aged > 50 years. Dermoscopy increased self‐confidence in analysing pigmented lesions ( P = 0·004), and dermoscopy users referred fewer patients to dermatologists. The number of biopsies was reduced in the dermoscopy users group ( P = 0·004). In total, 425 questionnaires were returned and analysed. Dermoscopy users took more time to evaluate a single pigmented lesion ( P = 0·015). Only 16·9% of physicians declared having received some training on dermoscopy, yet this number reached 47% for those owning a dermoscope. Their training was mostly short and recent. Overall 29·2% of the respondents said the main advantage was to reduce the number of referrals to the dermatologists ( P = 0·004), while its main disadvantage was the necessity of training (54·6%). Our responders declared they could spend seven working days on a dermoscopy training course. Conclusions: Our study demonstrates positive opinions regarding dermoscopy, despite a minority of French GPs using this technique in the areas surveyed. The need for formal training appears to be the main limitation to wider use. Appropriate and specifically designed training programmes should be offered. Abstract : What's already known about this topic? National surveys regarding the use of dermoscopy by general practitioners have been conducted mainly in Australia and Italy. The use by French general practitioners has never previously been described, despite dermoscopy being a useful tool for the diagnosis of melanoma. What does this study add? Dermoscopy provides new and important diagnostic criteria to diagnose melanoma more accurately and reliably. We report herein the first study evaluating the use of dermoscopy by general practitioners in France. We aimed to analyse the current use, opinions, teaching modalities and research in this field. Linked Comment: Rosendahl. Br J Dermatol 2016;175 :673–674 . Plain language summary available online